MEDIATION IN THE WORK OF HIGHER SCHOOL TEACHER - Yekaterina V. Ryabinina (Russian State Vocational Pedagogical University, 2015)
The purpose of this paper is to study modern conflictological situation in Russian society, which requires the widespread introduction of new technologies for the management of conflicts in the educational process and re-thinking of the teacher's role as a mediator to optimize the relationship process among students. Results. The author describes the stages of mediation and the specific work of the teacher-mediator in the educational organization and the requirements for their qualifications, demonstrates the types of activities of conflict resolution and their impact on the participants of conflict interaction. Particular attention is considered to the basic principles of mediation in the educational system. Scientific novelty. The author singles out the problems of mediation in the work of higher school teachers. The teacher defending the rights of students tries to resolve any disputes and conflicts with the interests of the disputing parties and social justice. Mediation as a form of alternative dispute resolution is becoming an integral part of the legal culture of our society. The article points to the need to enhance the conflict competence of teachers of higher schools. Practical significance. The research findings can be useful for psychologists, managers in the education system and teachers of higher education; conclusions proposed in the article can find practical implementation in teaching the course «Conflict Management». Presented theoretical material can be used for the formation and development of a mediation service in high school, should be the subject of further research in this area to find out alternative methods of dispute resolution in educational process.